DOI: 10.31274/etd-180810-2355
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment and fractionation of lignocellulosic biomass for production of biofuel and value-added products

Abstract: Introduction Materials and Methods Results and Discussion Conclusions Acknowledgements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 95 publications
(86 reference statements)
1
4
0
3
Order By: Relevance
“…Endo-cellulases attack the β-1,4-glycosidic bonds randomly, targeting the amorphous region along the cellulose structure and produce either cellobiose or glucose. On the other hand, exo-cellulases act on the linkages from the non-reducing end of cellulose releasing cellobiose as the main reaction product [36]. Similar patterns were observed for the hemicellulose-derived monosaccharides in this study.…”
Section: Enzymatic Hydrolysis Of Non-treated and Thermally Pre-treatesupporting
confidence: 84%
See 1 more Smart Citation
“…Endo-cellulases attack the β-1,4-glycosidic bonds randomly, targeting the amorphous region along the cellulose structure and produce either cellobiose or glucose. On the other hand, exo-cellulases act on the linkages from the non-reducing end of cellulose releasing cellobiose as the main reaction product [36]. Similar patterns were observed for the hemicellulose-derived monosaccharides in this study.…”
Section: Enzymatic Hydrolysis Of Non-treated and Thermally Pre-treatesupporting
confidence: 84%
“…According to the manufacturer's datasheet (Sigma Aldrich), cellulase contained mainly endo-and exo-cellulases, thus their documented synergistic activities led to the effective hydrolysis of cellulose and β-glucans [35,36]. Endo-cellulases attack the β-1,4-glycosidic bonds randomly, targeting the amorphous region along the cellulose structure and produce either cellobiose or glucose.…”
Section: Enzymatic Hydrolysis Of Non-treated and Thermally Pre-treatementioning
confidence: 99%
“…The ultra‐dissolution and release of hemicellulose in ZnCl 2 .4H 2 O (>95% of total hemicellulosic content ) (Table ) was a profound observation. Yoo et al reported up to 96% solvation of hemicellulosic content in corn stover dissolved in ZnCl 2 .4H 2 O, relating the high yield to the efficiency of the solvent's ability to fractionate biomass …”
Section: Resultsmentioning
confidence: 99%
“…Komponen terbesar penyusun TKKS terdiri atas 45,95% selulosa, 16,49% hemiselulosa dan 22,48% lignin (Wardani, 2014). Menurut Yoo (2012) dan North (2014) setiap komponen tersebut dapat diubah menjadi produk yang lebih bernilai guna dan bernilai jual. Selulosa yang merupakan komponen terbesar, dapat diolah menjadi sumber energi/bahan bakar cair berupa bioetanol, asam organik, pelarut, pelumas dan polimer.…”
Section: Pendahuluanunclassified
“…Hemiselulosa mengandung xilan yang terdiri atas unit-unit xilosa, dapat diolah menjadi etanol, xilitol (pemanis buatan), resin, dan nylon. Sementara itu, lignin dapat diolah menjadi bahan dasar kimia organik, batu bara dan bahan bakar padat (North, 2014;Yoo, 2012).…”
Section: Pendahuluanunclassified